A Cross-Platform Exploratory Study of International and Domestic Scholar Post Engagement on Social Media - Allison R Byrd; Catherine E. Sanders; Alexa Lamm (Journal of International Agricultural and Extension Education, 2023)
Social media use varies globally across cultures, even within extension services. Recognition of the contributions of international scholars at the universities where they serve also varies. Social media use in international scholars’ countries of origin may differ from that of their institution’s country, affecting social media engagement with a university’s posts featuring international scholars. Using the conceptual framework of audience segmentation, this study explored the differences in social media audience engagement between research themes and international and domestic scholars on Instagram and Twitter. Using a causal-comparative design, this study created Instagram and Twitter posts highlighting peer-reviewed research conducted by both international and domestic scholars at a United States university in a variety of research themes. Separate Instagram and Twitter posts were created for each scholar. Scholars were categorized by research theme and as either international or domestic. Engagement metrics were analyzed descriptively to explore the differences between research themes and international and domestic scholars across Instagram and Twitter audiences. Advances in food science and safety received the highest engagement rate on Instagram, but the lowest engagement rate on Twitter. International scholars received more engagement than domestic scholars in all categories on Instagram. Domestic scholars had higher mean engagements and engagement rates by impressions than international scholars on Twitter, but international scholars received more mean impressions. The results revealed a scholar’s research theme and status as either international or domestic may influence the level of social media engagement they receive on a specific social media platform. Recommendations for research are discussed.
Keywords: social media; audience segmentation; international scholars; Twitter engagement; Instagram engagement